PENGARUH PENGGUNAAN ENSIKLOPEDIA TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Sulistya Hapsari; Rahma Dwi Novitasari; Dimas Daffa Izzulhaq; Ika Dian Rahmawati (CV. Adiba Aisha Amira, 2026)
This study aims to determine the effect of encyclopedia use on the learning outcomes of fourth-grade students at SDN Socah 2, Bangkalan Regency. A quantitative approach was employed using a Pre-experimental Design with a One-Group Pretest-Posttest Design. The research sample consisted of all 18 fourth-grade students. Data were collected through pre-test and post-test instruments administered before and after the treatment, which involved learning using encyclopedias as instructional media. Data were analyzed using descriptive statistics to compare student learning outcomes before and after the intervention. The results showed an increase in the mean score from 82.94 (pre-test) to 85.94 (post-test). The minimum score improved from 53 to 66, and the maximum score increased from 93 to 100. Standard deviation decreased from 12.38 to 10.18 and variance from 153.35 to 103.70, indicating a more homogeneous distribution of scores after the treatment. It is concluded that the use of encyclopedias positively affects the learning outcomes of elementary school students by improving comprehension, fostering independent learning, and strengthening students' literacy culture.